Effect of Modified Atmosphere on Seed Mycoflora in Cauliflower Seeds - P.R. KUMAR; S.N. SINHA; S.K. LAL; SHIV K. YADAV; S.S. SINGH; ANUJA GUPTA (Seed Research, 2026)
The modified atmosphere (MA) containing 20% CO2 and 2% O2 is capable of controlling the incidence of seed mycoflora (fungal infestation) in cauliflower seeds. Low seed moisture contents kept seed-borne mycoflora low, by making the modified atmosphere more effective. Hence, it was concluded that hypercarbic atmosphere (20% CO₂) compounded with hypoxic condition (2% O₂) is highly efficient in controlling fungal infestation. However, an increase in amount of Aspergillus spp. as well as Penicillium spp. in modified atmospheres was noticed.